2005
DOI: 10.1073/pnas.0409072102
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery of human apolipoprotein E alters brain Aβ burden in a mouse model of Alzheimer's disease

Abstract: Apolipoprotein E (apoE) alleles are important genetic risk factors for Alzheimer's disease (AD), with the 4 allele increasing and the 2 allele decreasing risk for developing AD. ApoE has been shown to influence brain amyloid-␤ peptide (A␤) and amyloid burden, both in humans and in transgenic mice. Here we show that direct intracerebral administration of lentiviral vectors expressing the three common human apoE isoforms differentially alters hippocampal A␤ and amyloid burden in the PDAPP mouse model of AD. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
97
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(102 citation statements)
references
References 43 publications
2
97
1
2
Order By: Relevance
“…The result of this study is opposite to that of the majority of studies which demonstrated the protecting role of allele ε4 in AMD (7)(8)(9)(10)(11)(12)(13)(14). Therefore, the reasons why this allele is a risk factor for cardiovascular diseases and Alzhei-mer (EA) (1,17,19) and not for AMD is an enigma, considering moreover that it has some histopathological similarities with EA (1). In summary, our study proves a non-protecting association of allele ε4 with AMD.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The result of this study is opposite to that of the majority of studies which demonstrated the protecting role of allele ε4 in AMD (7)(8)(9)(10)(11)(12)(13)(14). Therefore, the reasons why this allele is a risk factor for cardiovascular diseases and Alzhei-mer (EA) (1,17,19) and not for AMD is an enigma, considering moreover that it has some histopathological similarities with EA (1). In summary, our study proves a non-protecting association of allele ε4 with AMD.…”
Section: Discussioncontrasting
confidence: 55%
“…We have no explanation for the association found between allele _4 and an earlier expression of AMD in women. Estrogens could be related to this difference, because it is known they interact with APOE at the level of the brain and are involved in the synthesis of the beta-amyloid peptid by microglya (17,18 Clinical studies have provided contradictory results for the association between AMD and different APOE gen alleles (12)(13)(14)(15). The result of this study is opposite to that of the majority of studies which demonstrated the protecting role of allele ε4 in AMD (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that MMPs, such as MMP-9, play important roles in regulating extracellular A␤ levels in brain , and our data demonstrating that apoE isoforms differentially determine the level of MMP-9 secretion from macrophages suggests that the reported effects of various apoE isoforms on amyloid deposition in vivo (Holtzman et al, 1999(Holtzman et al, , 2000Fagan et al, 2002;DeMattos et al, 2004;Dodart et al, 2005) may be due in part to differences in MMP-9 activity or secretion from apoE-expressing cells, including astrocytes, microglia, or macrophages. However, additional yet to be determined mechanisms may underlie the ability of macrophages to robustly degrade A␤ either in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…Other characteristics include synaptic dysfunction (5), decreased cerebral blood flow to the posterior portion of the left cingulate cortex (6), and cerebral endothelial dysfunction (7). Combinations of these and a variety of other factors may lead to neurodegeneration (8). Clinically, AD is defined by the presence of multiple cognitive alterations--characteristically amnesia and one or more of the following disturbances: aphasia, apraxia, agnosia, and alterations of normal executive functioning with progressive neurologic decline (9).…”
mentioning
confidence: 99%
“…DM2 and the APOE4 allele have been found to be associated with an increased amount of amyloid plaques in the hippocampus, increased amount of NFT and increased cerebral amyloid angiopathy (8,29,30). ApoE is a circulating lipoprotein, which, by binding the low density lipoprotein (LDL) receptor, promotes the intracellular metabolism of lipids (31)(32)(33).…”
mentioning
confidence: 99%